Renewable disulfide-based polyesters: highly cross-linked, vitrimers, and biodegradable materials - Gaglieri, Caroline [UNESP]; Alarcon, Rafael T.; dos Santos, Gabriel I. [UNESP]; Bannach, Gilbert [UNESP] (My University, 2024)
Due to the large application of polymeric materials, they have received great production demand and therefore increased the research about new synthesis technologies and sources, especially using renewable ones. In this sense, this work used the maleinized grape seed vegetable oil and a polyol with disulfide bonds to produce new renewable materials. The molar proportion between them was evaluated and thermal analysis, mid-infrared spectroscopy, gel, and bio-based contents were used to determine the dependence on properties of disulfide content (2-hydroxyethyl disulfide). Besides the thermal stability, which decreased with the disulfide increasing, the properties of maximum degradation rate, cross-linking density, Young’s modulus, and resistance to basic hydrolysis were high. All materials present elevated bio-based content and completely degrade under basic conditions after 8 h. As thermosetting, they were non-soluble even in nonpolar solvents and do not melt under heating; however, cutting and heating them at mild conditions reshaped them. Therefore, they can be considered as vitrimers.
Keywords: Disulfide bonds; Renewable polymer; Solvent-free synthesis; Vegetable oil derivatives